Investigating Spoken English Errors: Pronunciation and Grammar among Students of Non-English Majors - Rizki, Julia; Ismar, Randila Tiayu (Pencerah, 2025)
Exploring students’ errors can reveal the students’ knowledge about the target language, and the teacher then can focus on the students’ learning problems. Speaking is considered the most like to contain errors among the four language skills. This study aimed at investigate pronunciation and grammatical errors committed by EFL learners in speaking skills. It focuses on classifying pronunciation and grammatical errors using the Target Modification Taxonomy proposed by Carl James. The method used in this study was a case study. In a total, 20 students in an International Tourism College in Aceh were involved as participants. The data were collected by recording the students’ utterances in a speaking test. Findings indicate that there were four types of pronunciation errors and five types of grammatical errors. In pronunciation errors, the learners committed errors in omission, overinclusion, misordering, and misselection. In terms of grammatical errors, the students made mistakes in omission, overinclusion, misordering, misselection, and blends. These findings highlight the influence of students’ first language (Indonesian) and insufficient exposure to English input. Pedagogically, the results suggest that teachers should integrate minimal pair drills to address common pronunciation problems and provide explicit instruction on subject-verb agreement through focused practice activities